2020
DOI: 10.1111/ijlh.13349
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of Prothrombin Time/International Normalized Ratio (PT/INR)

Abstract: The prothrombin time (PT) represents the most commonly used coagulation test in clinical laboratories. The PT is mathematically converted to the international normalized ratio (INR) for use in monitoring anticoagulant therapy with vitamin K antagonists such as warfarin in order to provide test results that are adjusted for thromboplastin and instrument used. The INR is created using two major PT ‘correction factors’, namely the mean normal PT (MNPT) and the international sensitivity index (ISI). Manufacturers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 47 publications
0
56
0
2
Order By: Relevance
“…Heparin binds to antithrombin via its pentasaccharide, catalyzing the inactivation of thrombin and other clotting factors [ 1 ]. Warfarin, a vitamin K antagonist used to hamper γ-carboxylation of vitamin K-dependent coagulation factors, has also been used historically as an anticoagulant [ 1 , 2 ]. Drug monitoring in clinical laboratory tests is required when using these drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Heparin binds to antithrombin via its pentasaccharide, catalyzing the inactivation of thrombin and other clotting factors [ 1 ]. Warfarin, a vitamin K antagonist used to hamper γ-carboxylation of vitamin K-dependent coagulation factors, has also been used historically as an anticoagulant [ 1 , 2 ]. Drug monitoring in clinical laboratory tests is required when using these drugs.…”
Section: Introductionmentioning
confidence: 99%
“…As PT reflects exogenous coagulation function, an increase in PT implies a hypocoagulability status in FIGO grade 3 compared with FIGO grade 2. 12 FDP and D-dimer are degradation products created by fibrinolytic enzymes acting on crosslinked fibrin, 13 and the increase in FDP and D-dimer levels might imply fibrinolytic hyperactivity in FIGO grade 3. The association identified by this study indicated hypocoagulability and hyperfibrinolysis status along with PAS deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…VICC is characterised by procoagulant toxins activating various clotting factors, leading to activation of the coagulation cascade, factor consumption and a resultant consumption coagulopathy [4,7]. VICC presents with a reduced or unrecordable fibrinogen; prolonged or unrecordable PT (or its international normalised standardised equivalent, the international normalised ratio (INR) [33]) and activated partial thromboplastin time (APTT); and an elevated D-dimer [34]. It is an acute and transient coagulopathy associated with a risk of bleeding, worse in snake venoms that also contain metalloproteinases.…”
Section: Association With Envenoming By Snake Genera/species Causing Viccmentioning
confidence: 99%